2016
DOI: 10.1021/acs.jpcc.5b11460
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Observation of a Self-Assembled Monolayer Formation of Octadecyltrimethoxysilane on a Silicon Oxide Surface Using a High-Speed Atomic Force Microscope

Abstract: High-speed AFM measurements: High-speed AFM measurements were performed on a Research Institute of Biomolecule Metrology (Tsukuba, Ibaraki, Japan) Nano Explorer Highspeed Atomic Force Microscope with an Olympus (Tokyo, Japan) BL-AC10FS cantilever. A Si(100) substrate was cut into 2x2 mm 2 pieces, and the surface of each piece was oxidized by using a UV ozone cleaner. After the substrate was immersed in SAMLAY ® -A with a volume of 120 L, topographical images were collected every 2 sec with a frame size of 3x3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
(56 reference statements)
0
18
0
Order By: Relevance
“…35,36 Self-assembled monolayers of ODTS, OTMS and Cl-DMOS on SiO 2 surfaces has been reported previously. 26,27,36 Although the determination of the additional layer formation was not conducted, the increase in size of the SiO 2 NPs as observed on TEM micrographs upon modification using the silane reagents indicated the formation of an additional layer as suggested by others. 26,27,36 wileyonlinelibrary.com/jctb…”
Section: Results and Discussion Tem Analysis Of Sio 2 Npsmentioning
confidence: 92%
See 1 more Smart Citation
“…35,36 Self-assembled monolayers of ODTS, OTMS and Cl-DMOS on SiO 2 surfaces has been reported previously. 26,27,36 Although the determination of the additional layer formation was not conducted, the increase in size of the SiO 2 NPs as observed on TEM micrographs upon modification using the silane reagents indicated the formation of an additional layer as suggested by others. 26,27,36 wileyonlinelibrary.com/jctb…”
Section: Results and Discussion Tem Analysis Of Sio 2 Npsmentioning
confidence: 92%
“…M4 is the PVDF nanofibre membrane embedded with OTMS‐modified SiO 2 NPs. The OTMS molecule is characterized by a long aliphatic carbon chain (CH 3 (CH 2 ) 17 ‐ as in the case of other silane agents (ODTS and Cl‐DMOS), although their anchor functional groups are different: on OTMS it is (‐Si‐OCH 3 ) 3 , on ODTS it is (‐Si‐ClCH 2 ) 3 and on Cl‐DMOS it is (‐Si‐Cl 3 ) 3 . The anchor groups on OTMS are more hydrophobic due to the presence of bulky nonpolar CH 3 groups.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, this notion has been reported in literature before. For instance, an in situ study by Iwasa etal using AFM has observed morphological behaviour showing islands growing from a nucleation site on the surface with minimal surface bonds and further supports the proposed mechanisms that are thought to underpin the oscillatory behaviour observed here.…”
Section: Resultsmentioning
confidence: 99%
“…The OTMS molecule is characterized by a long aliphatic carbon chain (CH 3 (CH 2 ) 17 ‐) where the anchor group is (‐Si‐OCH 3 ) 3 . Furthermore, the anchor groups on ODTS and Cl‐DMOS are (‐Si‐ClCH 2 ) 3 and (‐Si‐Cl 3 ) 3 , respectively . The anchor groups on OTMS are more hydrophobic due to the presence of bulky non‐polar CH 3 groups.…”
Section: The Use Of Nanoparticles In Membrane Modificationmentioning
confidence: 99%
“…Furthermore, the anchor groups on ODTS and Cl-DMOS are (-Si-ClCH 2 ) 3 and (-Si-Cl 3 ) 3 , respectively. [68][69][70][71][72][73][74] The anchor groups on OTMS are more hydrophobic due to the presence of bulky non-polar CH 3 groups. The presence of strong electron withdrawing atoms such as chlorine and oxygen in Cl-DMOS and ODTS cause an uneven distribution of electrons, which could subsequently induce a minimal polarity on one end of the molecule, and slightly reduce its hydrophobicity.…”
Section: The Use Of Nanoparticles In Membrane Modificationmentioning
confidence: 99%